An Inquiry-Based Approach to Critical Literacy: Pedagogical Nuances of a Second Grade Classroom - Beach, Pamela; Cleovoulou, Yiola (Alberta Journal of Educational Research, 2014)
This case study explores the pedagogy and practices of an elementary school teacher who combines inquiry pedagogy and critical literacy. The authors gathered data for this analysis by conducting two interviews with a classroom teacher and observing classroom practices 12 times over a 6 month period. Through a general inductive approach to analysis, trends emerged that showed the classroom teacher used practices that combined traditional inquiry pedagogy for critical literacy development. This research provides insight into how this elementary teacher negotiated and connected inquiry to critical literacy. Furthermore, the findings can inform scholars and teacher educators of successful teaching strategies as they prepare future generations of elementary teachers. Cette étude de cas explore la pédagogie et les pratiques d’une enseignante à l’élémentaire qui allie pédagogie d’enquête et littératie critique. La cueillette de données s’est faite par deux entrevues auprès d’une enseignante titulaire et douze observations en salle au cours de six mois. Une approche inductive à l’analyse a révélé des tendances indiquant que l’enseignante employait des pratiques qui intègrent une pédagogie d’enquête traditionnelle au développement de compétences essentielles à la littératie. Cette recherche donne un aperçu des démarches de l’enseignante pour négocier et lier enquête et littératie. De plus, les résultats présentent aux chercheurs et aux formateurs d’enseignants des stratégies pédagogiques efficaces et fructueuses dont peuvent profiter les générations futures d’enseignants à l’élémentaire.